Green Taxation on Competitiveness: The Effect of the ISP Tax on the Portuguese Retail Sector of Road Fuels - Oliveira, David; Mendes, Isabel (International Journal of Energy Economics and Policy, 2017)
There hasn’t been much clarity on the issue regarding the effects of green taxation on competitiveness as researchers use different conceptual and methodological parameters in defending their arguments. In this sense, and given that most studies provide mixed results, we aimed to contribute to the clarification of the issue with the analysis of a specific case-study. Through the effect of the ISP tax (Imposto sobre Produtos PetrolÃferos e EnergÃ©ticos) on the competitiveness of the Portuguese retail sector of road fuels we intended to demonstrate that a microeconomic approach is more enlightening than a meso/macroeconomic one, and that the effect of environmental policy on competitiveness will depend on the characteristics of the firms and of the markets to which they sell. Our findings come close to the Porter hypothesis. Keywords: Fiscal Policy; Environmental Tax; Energy Demand. JEL Classifications: E62; Q41; Q52